Canine visceral leishmaniasis: study of methods for the detection of IgG in serum and eluate samples - Figueiredo, Fabiano B.; Madeira, Maria F.; Nascimento, Lílian D.; Abrantes, Tuanne R.; Mouta-confort, Eliame; Passos, Sonia Regina L.; Schubach, Tânia Maria P. (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
The Brazilian Ministry of Health recommends the culling and euthanasia of dogs with a positive serological test for canine visceral leishmaniasis (CVL). In the Municipality of Rio de Janeiro, the technique used for the diagnosis of CVL is the indirect fluorescent antibody test (IFAT), using blood samples eluted on filter paper (eluate). A dog survey was conducted over a period of one year in the region of Carapiá, in order to evaluate the diagnosis of CVL in this region. All animals underwent clinical examination, and blood samples (serum and eluate) were collected for analysis by enzyme immunoassay (ELISA) and IFAT. A skin biopsy was obtained for parasitological examination (culture). A total of 305 animals were studied and Leishmania chagasi was isolated from nine animals. Sensitivity and specificity were 100% and 96.6% for ELISA, respectively, 100% and 65.5% for IFAT (cut-off at a 1:40 dilution), 100% and 83.4% for IFAT (cut-off at a 1:80 dilution), and 22.2% and 97.0% for eluate IFAT. In conclusion, ELISA was the best tool for the diagnosis of CVL among the serological techniques tested. The present results suggest the need for a better evaluation of filter paper IFAT as the only diagnostic method for CVL in the Municipality of Rio de Janeiro.